Spatial distribution of phytophagous insects, natural enemies, and pollinators on Leucaena leucocephala (Fabaceae) trees in the Cerrado - Joyce Gomes Damascena, Joyce Gomes; Leite, Germano Leão Demolin; Silva, Farley William Souza; Soares, Marcus Alvarenga; Guanabens, Rafael Eugênio Maia; Sampaio, Regynaldo Arruda; Zanuncio, José Cola (Florida Entomologist, 2017)
Leucaena leucocephala (Lam.) de Wit (Fabaceae) is widely used to regenerate degraded landscapes in tropical and subtropical regions and serves as a protein source for animals in agrosilvopastoral systems. Thus, our objective was to assess the spatial distribution of insects on the tree crown (vertical: upper, middle, and basal canopy; horizontal: north, south, east, and west) and leaf surfaces (adaxial and abaxial) of L. leucocephala. Phytophagous insects, natural enemies, and pollinators were quantified fortnightly in 20 trees for 2 yr. North-facing tree branches had the greatest numbers of phytophagous insects, natural enemies, and pollinators. Branches facing west had the most species-rich and biodiverse phytophagous and pollinator assemblages, whereas for natural enemies, species richness and biodiversity were greatest on branches facing north or south. The greatest numbers of individuals and highest levels of species richness of phytophagous insects, natural enemies, and pollinators were observed in the upper and middle parts of the L. leucocephala canopy. The most individuals and highest levels of species richness and biodiversity for phytophagous insects, natural enemies, and pollinators were observed on the abaxial face of L. leucocephala leaves. The species with the highest abundance and k-dominance (common or constant species) on L. leucocephala trees were the phytophagous insects Trigona spinipes F. (Hymenoptera: Apidae: Meliponinae) and Tropidacris collaris Stoll (Orthoptera: Romaleidae) and the natural enemies Camponotus sp.2 (Hymenoptera: Formicidae) and Brachymyrmex sp. (Hymenoptera: Formicidae). These results can inform strategies related to pest control and maintenance of natural enemies and pollinators in L. leucocephala plantations. Biopesticide application, for example, may be more effective at eliminating target organisms if directly applied on their preferred sites, and a targeted application can minimize negative effects for non-target organisms.
Keywords: Abundance; Biodiversity; Natural enemies; Savannah; Abundancia; Biodiversidad; Enemigos naturales; Sabana